Composition and Decomposition: On Thornton Dial’s Aesthetics - Siyothula, Nomalanga (University of the Witwatersrand, Johannesburg, 2024)
In this study I explore how Composition and Decomposition: On Thornton Dial’s Aesthetics can be theorised and understood within black studies but based on three selected assemblages in his art practice. The study will engage in three forms of Dial’s aesthetics: The aesthetics of the black social life, the aesthetics of ruins and disposability and the aesthetics of revitalisation and care. It is in this form that Dial’s work will be meditated upon. It will do so by centering Composition and Decomposition as the analytical tools. It is a study that will engage in the protocols of black aesthetics, making and unmaking for there to be generativity. So, for this to come into being it is important to understand Dial as a figure in order to arrive at new ways of decolonising black aesthetics.
A research report Submitted in fulfillment of the requirements for a Master of Arts , In the Faculty of Humanities , School of Arts, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Composition and Decomposition; Aesthetics of the black social life; Aesthetics of ruins and disposability; Aesthetics of revitalisation and care; Decolonising black aesthetics; SDG-4: Quality education; SDG-17: Partnerships for the goals